Carcinoma cuniculatum of the lower gingiva masked with leukoplakia: A case of difficult diagnosis. Issue 3 (May 2021) - I, Takashi; Miura, Kei-ichiro; Kakehashi, Hiroe; Shiraishi, Takeshi; Egashira, Kazuhiro; Asahina, Izumi
Abstract: Oral carcinoma cuniculatum (CC) is defined as a rare variant of low-grade, well-differentiated squamous cell carcinoma (SCC). The diagnosis of oral CC has remained very difficult, due to the lack of familiarity of clinicians and pathologists with this pathology. Oral CC is therefore often initially diagnosed as osteomyelitis, dental abscess, or keratocyst. Histopathologically, oral CC is characterized by keratinized tissue lined by epithelium with no or only mild cellular atypia, which invades locally and rapidly into the bone. In the present case, oral CC developed from a state of leukoplakia. A white lesion on the lower gingiva was pathologically diagnosed as epithelial dysplasia without cellular atypia, but kept recurring after repeated local removal. Two years and nine months after the first visit, the lesion showed rapid invasion into alveolar bone, in which richly keratinized tissue was observed. The patient then underwent marginal mandibulectomy and the tumor was pathologically diagnosed as SCC. Based on the clinical follow-up, we suspected the lesion represented oral CC and wide resection with reconstructive surgery was performed. If oral CC can be diagnosed at an earlier stage, the area of resection can be minimized. As oral CC tends to be misdiagnosed because of a lack of evidence of malignant tumor, both clinicians and pathologists should consider oral CC when leukoplakia shows frequent recurrence.